Les dangers de la navigation et de la pêche dans l'Atlantique Français au 18e siècle - Landry, Nicolas (The Northern Mariner / Le marin du nord, 2015)
A central theme in the historiography of the Ancien Régime in Canada has always been the ocean crossing between France and New France. Despite the advancement of scientific knowledge during the 18th century, navigation remained a major challenge for those wishing to travel from France to its overseas colonies. Storms were a constant threat, as was piracy and, for much of the era, war. Marine disasters were frequent and took a heavy toll among the officers, crews and passengers. More comprehensive research on shipwrecks during the French Régime in Canada is needed. The present article seeks to further our knowledge of the circumstances prevailing aboard endangered ships, how local authorities responded to the disasters on their shores, especially care for survivors and salvage of cargoes, and how they reported these events and challenges to Versailles.